Modelagem e simulação da dispersão de metano no reservatório de Santo Antônio-Rondônia - Menezes Júnior, Evanízio Marinho de (2017)
In this work, a mathematical model of the dispersion of atmospheric methane is proposed for the lake formed by the damming of the Madeira River in the state of Rondônia for the use of model is simulated the surface dynamics of methane in the region of the Santo Antônio Hydroelectric Dam at Rondônia. The model was elaborated from a general diffusion-advection-reaction for methane. The numerical approximation was obtained with the use of the finite element method (MEF) for the spatial approximations and the Crank-Nicolson method for temporal approximations. The approach provided scenarios for the directional fields of methane fluxes for different time periods and the results suggest a relation to the location in the reservoir, with flooded biomass, with dark waters and with advective components for the dispersion of the gas.